THE IMPACT OF JOB SATISFACTION ON EMPLOYEE PERFORMANCE AT CIREBON POLTEK COMPUTER SCIENCE COLLEGE - Renyta Febryani (Journal Of Resource Management, Economics And Business, 2023)
Purpose: This study aims to examine the impact of job satisfaction on employee performance at Cirebon Poltek Computer Science College. Research Methodology: Quantitative descriptive research; population: 30 employees; sampling method: census; tools: questionnaires, structured interviews; software: SPSS for data analysis; methods: inferential analysis, linear regression. Results: Job satisfaction positively affects employee performance, with significant correlation found. Limitations: The study is limited to a single institution, which may restrict the generalizability of the findings Contribution: This research is beneficial for human resource management, organizational behavior, and educational institutions aiming to enhance employee performance through improved job satisfaction.